Peduli Lingkungan, Adat dan Budaya di Desa Mohiyolo dan Pengembangan Kawasan Wisata Air Terjun Desa Bontula - Jumiati Ilham; Muh Yusuf Tuloli; Arfan Usman Sumaga (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
The implementation of the Thematic KKN this time is somewhat different from previous years, where according to the Term of Reference (TOR) the Work Program or program topic is not determined, but students will develop a work program based on the results of the assessment of village needs and the results of coordination with the community and village government. Therefore, the theme of the activities that become the Core Program of KKN will only be known after students conduct field observations and assessments. Based on the results of the community needs assessment, it was found that the core programs in 2 (two) villages were the locations of the KKN (Posko) namely: 1). Mohiyolo village, Asparaga sub-district, Gorontalo district, are: Caring for the Environment, Customs and Culture in Mohiyolo Village, and 2). Bontula Village, Asparaga District, Gorontalo Regency, carries the core program of Waterfall Tourism Area Development in Bontula Village. The implementation of the Thematic Community Service Program in Developing Villages has resulted in or can form: 1). Village cares for the Environment, Green and Free from flooding; 2) The community cares about customs and culture; 3) The younger generation thinks critically through concern for literacy; 4) Increasing village income through the development of tourism potential, especially the Bontula waterfall; 5) Increasing public knowledge regarding the importance of continuing education in order to create superior and educated human resources; 6) Increasing the number of people who carry out vaccinations to support government programs in accelerating mass vaccination; and 7) Increasing community participation related to environmental awareness through the construction of pilot waste bins.